HEALTH EXAMINATION AND EDUCATION ON THE USE OF CHOLESTEROL, URIC ACID, AND BLOOD SUGAR MEDICINE FOR THE COMMUNITY OF SUNGAI BAWANG VILLAGE, MUARA BADAK DISTRICT, KUTAI KARTANEGARA - Muh. Taufiqurrahman; Adhe Septa Ryant Agus; Awan, Kevin Imanuel; Gilbert Luhat, Martin (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
Degenerative diseases that many people suffer from, including heart disease, stroke, hypertension, diabetes mellitus, cancer, and chronic kidney failure, have increased. In demographic data referring to the 2018 Riskesdas, for example, strokes increased to 10,9% from the previous 7%, and diabetes mellitus increased from 6.9% to 8.5% in 2018. Hypertension experienced the highest increase among diseases, from 25.8% to 34.1%. Management of degenerative diseases is through implementing community service activities carried out by lectures from the Study Program of Pharmacy undergraduate at STIKES Dirgahayu Samarinda to implement the tridharma obligations of higher education. The activity was held on Saturday, November 18, 2023, at Lamin Adat Sungai Bawang Village, Muara Badak District, Kutai Kartanegara. This activity aimed to conduct health checks for the community, from children to adults, and health education, especially controlling non-communicable diseases. The method used was education, free examination, and treatment for the community which consists of laboratory examinations, health consultations, pharmaceutical services, and health education, as well as evaluation when the activites have been completed. Based on the activities that have been carried out, it was known that one hundred and five residents came for an examination, then from screening for blood sugar, cholesterol, and uric acid tests, forty-seven people exceeded normal parameters, while ninety-eight received drug therapy.